PERBEDAAN LAMA PAPARAN SINAR UV-C TERHADAP PENURUNAN JUMLAH ANGKA KUMAN PADA ALAT MAKAN DI INDUSTRI TEKSTIL (Jurnal Kesehatan Siliwangi, 2021)
Sanitation of cutlery is intended to kill vegetative microbial cells left on the surface of cutlery. PT.X as one of the textile industries, provides canteen facilities to support the productivity of its workers. A total of 18 pieces or 9% of the 200 cutlery plates at PT.X did not meet the requirements according to Permenkes No. 1096 of 2011, the germ number is 524 colonies/cm2 of cutlery. This study aims to determine the difference in the length of exposure to radiation (10 minutes, 20 minutes, and 30 minutes) on the decrease in the number of germs on cutlery at PT.X. The cutlery used as a sample was 18 pieces. Based on the results of the study, it was known that there was a decrease in the number of germs before and after UV-C irradiation. Radiation with a long exposure of 10 minutes reduces the germ number by 63.12%, irradiation with a length of exposure of 20 minutes reduced the number of germs by 80.84% ​​and irradiation with a length of exposure of 30 minutes reduced the number of germs by 99.84%. The effective decrease occurred at 30 minutes of exposure.